If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 1 = -3(2x + 1) + x Reorder the terms: 1 + -6x = -3(2x + 1) + x Reorder the terms: 1 + -6x = -3(1 + 2x) + x 1 + -6x = (1 * -3 + 2x * -3) + x 1 + -6x = (-3 + -6x) + x Combine like terms: -6x + x = -5x 1 + -6x = -3 + -5x Solving 1 + -6x = -3 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 1 + -6x + 5x = -3 + -5x + 5x Combine like terms: -6x + 5x = -1x 1 + -1x = -3 + -5x + 5x Combine like terms: -5x + 5x = 0 1 + -1x = -3 + 0 1 + -1x = -3 Add '-1' to each side of the equation. 1 + -1 + -1x = -3 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = -3 + -1 -1x = -3 + -1 Combine like terms: -3 + -1 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 6y+11=43 | | X^2-15x+12=-6+4 | | 5x-3(x-1)-39= | | (2+3c)(4+6c+9c)= | | (2a-1)(a+3a+5)= | | 435*13= | | X+3=-3-5 | | 46.1*46.1=18.5*18.5+2(11.17)x | | 2(3x-5)=-(x-11) | | 2s-2=2 | | (a+2a-9)(a+3)= | | -15.00+2.00w=5 | | 12+7y-2=52 | | (y+3y-6)(2y+3)= | | 0=2x^2+6kx+8 | | 7r^2-14r-7=0 | | A=5W+10Z | | 2.00r-15.00=9 | | 12x-8=16x+4 | | 4x^2-3=x^2-11x | | (3x+2y)(2y+3x)= | | -4g+6=14 | | 6(x)-x=0 | | (z-2x)(z-2x)= | | 0.015x-0.030=0.030 | | 76=b+4 | | 3y(2+4y+5y^2)= | | 4(x-5)-7-5(3-2x)= | | (a+b)(2a-3b)= | | g-92=-74 | | (7y-4t)(2y+5t)= | | 2m+18=5m-12 |